PENERAPAN STRATEGI METAKOGNITIF UNTUK MELATIH PENALARAN FORMAL DALAM PEMBELAJARAN FISIKA PADA SISWA KELAS X SMA IT AL-ITTIHAD PEKANBARU - Setiorini, Fenny Setiorini; ', Azizahwati; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aimed to describe the ability of formal reasoning in students class X SMA IT AL-Ittihad with metacognitive strategies. The subjects were science students class x totaling 19 person. Data collection instrument in this research is the formal reasoning ability test consisting of 15 items about reasonable option. Analysis of data in this research is descriptive analysis to see an overview of the result of formal reasoning ability of students to learn using the criteria of absorption, enhancement of formal reasoning ability, and effectiveness of learning. From the analysis of the data shows : the averages absorption class is 71.9% with the good category, each indicator has increased formal reasoning, and declared effective learning effectiveness. Therefore, the application is declared effective metacognitive strategies to train and improve the ability of formal reasoning in physics learning in class X SMA IT AL-Ittihad Pekanbaru. Keywords: Metacognitive strategies, formal reasoning, temperature and heat.